Model Terpadu Sufisme, Psikologi, dan Sains dalam Terapi SEFT untuk Stres Mahasiswa Akibat Skripsi - Suroyya, Naharin (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Many students suffered stress when worked the thesis. In this research, researcher used SEFT to reduce college student’s thesis stress. The Problem in this research was how much influence and effectiveness percentage of SEFT. This research was experimental research that was done UIN Sayyid Ali Rahmatullah Tulungagung by 10 samples (5 respondents in experimental group and 5 respondents in control group). Based on the count results of Mann Whitney with p-value=0,009 and á=0,05 showed experimental group and control group had difference significant (p-value < á). Whereas, the count results Wilcoxon Signed Rank Test with p-value=0,042 and á=0,05 showed that SEFT was effective in reducing college student’s thesis stres (p-value < á). In addition, the count results of effectiveness percentage SEFT used Sumbangan Efektif Regresi Linier produced 88,3% so that the effectiveness level of SEFT was as many of 88,3%.